Higher Education minister surveys UMP readiness in handling Covid-19 outbreak - Mohd Ferdaus, Musa (2020)
The Higher Education Minister, Dato’ Dr. Noraini Ahmad visited Universiti Malaysia Pahang (UMP) on 10 April 2020 to survey the readiness of the university to face the Covid-19 outbreak.